Identification of Anticancer Active Compound from GC-MS Test Results of Zodia Leaves (Evodia suaveolens) Ethanol Extract - Ghea Dionita Sanora; Elly Yana Mastura; Muhammad Ongky Muji Handoyo; Erlix Rakhmad Purnama (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2019)
Cancer is estimated to be the second leading cause of death globally in 2018. The background of the study was the prevalence of cancer in Indonesia in 2018 reaching 775.120 people. Treatments such as surgery, chemotherapy, radiotherapy, immunotherapy, and hormone therapy have negative side effects. Herbal medicine is an alternative treatment with lower side effects that can reduce the side effects of existing treatments. The aim of this study was to identify the results of GC-MS active compounds from ethanol extract of zodia leaves which have the potential as anticancer. The method of this research was observational research through scientific literature. GC-MS results showed 22 active compounds contained in ethanol extract of zodia leaves. Based on the literature searching, there are 17 active compounds that have potential to be anticancer. Menthofuran; evodone; Bicyclopentene; Delta-Selinene; 3,5,7-Octatrien-2-Ol, 2,6-Dimethyl; Aromadendrene oxide 2; Alpha-bisabolol; 2,4-Dimethyl-2,4-Heptadienal; Phytol; Squalene; Beta-Tocopherol; D-alpha-Tocopherol; Stigmasta-5,23-dien-3.beta.-ol; (23S)-ethylcholest-5-en-3.beta.ol; 24,25-Dihydrolanosterol; Lanosterol; and Obtusifoliol. The compounds are targeted in breast, lung, and ovarian cancer.